Front Cover: Simultaneous quantification of three tropane alkaloids in goji berries by cleanup of the graphene/hexagonal boron nitride hybrids and ultra‐high‐performance liquid chromatography tandem mass spectrometry. Issue 18 (21st September 2020) - Zhao, Weihua; Shi, Yanping
Abstract : DOI: 10.1002/jssc.202000520 The cover picture shows that ultra high performance liquid chromatography with tandem mass spectrometry could be an effective tool to detect and quantify atropine, anisodamine, scopolamine in Goji berries together with the modified QuEChERS method, which used the graphene/hexagonal boron nitride hybrid as cleanup adsorbent to minimize matrix effects. It is successfully applied to evaluate the safety of Goji berries collected from China, suggesting its applicability and suitability for the routine analysis of three tropane alkaloids in Goji berries.